RELATIONSHIP BETWEEN DIGITAL FUND TRANSFERS AND FINANCIAL PERFORMANCE OF EQUITY BANK, KAMPALA BRANCH; A DESCRIPTIVE, CORRELATIONAL AND CROSS-SECTIONAL STUDY. - David Mugabi; Murishid Kamya; Edmand Bakashaba (Student's Journal of Health Research Africa, 2023)
Background